LINC-24. Survival and genetic evaluation of patients diagnosed with choroid plexus tumor treated at a Brazilian institution. (3rd June 2022) - Oliveira, Milena; Silva, Nasjla; Cappellano, Andrea; Rodrigues, Jessica; Almeida, Daniela; Cavalheiro, Sergio; Dastoli, Patricia; Silva, Frederico; Seixas, Maria Teresa; Lima, Fernanda
Abstract: INTRODUCTION: Choroid plexus tumors (CPT) are rare intraventricular neoplasms of epithelial origin. They usually occur in the 2nd year of life, corresponding to 0.4-0.6% of intracranial tumors in this age group. They are classified, according to WHO 2021: choroid plexus carcinoma (CPC), atypical choroid plexus papilloma (ACPP) and choroid plexus papilloma (CPP). Li-Fraumeni syndrome (LFS) is present in 50% of patients with CPC. In Brazil, the TP53p.R337H mutation affects 0.3% of the population in the South/Southeast. OBJECTIVE: Evaluate the genetic assessment and overall-survival (OS) of patients with CPT treated at IOP/GRAACC/UNIFESP. PATIENTS/METHODS: Between 1995-2021, 48 patients were diagnosed with CPT in our institution, 27 CPC, 18 CPP and 3 ACPP. From 2012-2021 patients were referred for genetic evaluation, 16 of which had CPC (2 had previously CPP). Family history for neoplasms was present in 87.5%, 37.5% compatible with Li-Fraumeni Syndrome (LFS) of which 50% with positive mutations. The molecular investigation of TP53 gene in patients with CPC was performed and positive in 62, 5%:R337H(6 patients), R110C*, R158H*, H179R*, R196* (*1 patient each). For those with R337H, p53 protein immunohistochemistry resulted in 90-100% positivity. Treatment strategies consisted of surgery with gross total resection being achieve in all ACPP, 94, 4% CPP and 55, 5% CPC. Chemotherapy was performed in only 1 case of ACPP and all CPC with a variety of schemas, including high dose of chemotherapy and autologous bone marrow transplant for slow responders or recurrent disease. The three- and five-years OS for CPC was 72.5% and 61.7%, respectively. For CPP and ACPP 5y OS was 100%. CONCLUSION: The present study is in agreement with the literature showing an excellent survival for CPP and ACPP but an inferior outcome for patients with CPC and TP53 mutation despite being assisted by a well-prepared multidisciplinary team with an adequate treatment.